Sejarah Perkembangan Yayasan Nurul Hasanah Surabaya Tahun 1996-2021 M - Markhumah, Nava Khurin; Juma’, Juma’ (Qurthuba: The Journal of History and Islamic Civilization, 2022)
This study focuses on three problems, namely: (1) What is the history of the establishment of the Nurul Hasanah Foundation in Surabaya. (2) How is the development of the Nurul Hasanah Foundation in Surabaya. (3) What are the supporting and inhibiting factors for the development of the Surabaya Nurul Hasanah Foundation. This thesis uses a historical research method with four steps, namely heuristics, verification, interpretation, and historiography. Meanwhile, the approach used in this study is a historical approach and sosiological approach. Meanwhile, the theory used in this research is social institutions by Paul B. Horton and Chaster L. Hunt along development theory by G. Kartasapoetra. Based on research studies, it can be concluded that: (1) The Nurul Hasanah Foundation was founded by Susila Sukmawati in 1996. (2) The developments that occur at the Nurul Hasanah Foundation cover three aspects, including: facilities and infrastructure, the number of foster children, and program activities. (3) The supporting factors for its development include: partnership with Yatim Mandiri, the enthusiasm and enthusiasm of the management, and the trust of donors. Meanwhile, the factors that hinder the development of this foundation include: no fixed allowance from the government, the negative views of the surrounding community, and limited facilities and infrastructure.